Enhanced Morbidity of Pectoralis Major Myocutaneous Flap Used for Salvage after Previously Failed Oncological Treatment and Unsuccessful Reconstructive Head and Neck Surgery - Christiana Maria Ribeiro Salles Vanni; Leandro Luongo de Matos; Mário Paulo Faro Junior; Jossi Ledo Kanda; Cláudio Roberto Cernea; Lenine Garcia Brandão; Fábio Roberto Pinto (The Scientific World Journal)
Introduction. The reconstruction of complex cervicofacial defects arising from surgical treatment for cancer is a real challenge for head and neck surgeons, especially in salvage reconstruction surgery and/or failed previous reconstruction. The pectoralis major myocutaneous flap (PMMF) has been widely used in these specific situations due to its reliability and low rate of failure or complications. Objectives. Identify factors that determine complications and influence the final outcome of the reconstructions with PMMF in salvage cancer surgery or in salvage reconstruction. Methods. A cross-sectional study design was used to evaluate a sample including 17 surgical patients treated over a period of ten years that met the inclusion criteria. Results. Reconstruction was successful in 13 cases (76.5%), with two cases of partial flap loss and no case of total loss. Complications occurred in 13 cases (76.5%) and were specifically related to the flap in nine instances (52.9%). An association was identified between the development of major complications and reconstruction of the hypopharynx (𝑃=0.013) as well as in patients submitted to surgery in association with radiation therapy as a previous cancer treatment (𝑃=0.002). The former condition is also associated with major reconstruction failure (𝑃=0.018). An even lower incidence of major complications was noted in patients under the age of 53 (𝑃=0.044). Conclusion. Older patients, with hypopharyngeal defects and submitted to previous surgery plus radiation therapy, presented a higher risk of complications and reconstruction failure with PMMF.